Factors influencing implementation of interventions to promote birth preparedness and complication readiness - Andrea Solnes Miltenburg; Yadira Roggeveen; Jos van Roosmalen; Helen Smith (BMC, 2017)
Abstract Background The recent WHO report on health promotion interventions for maternal and newborn health recommends birth preparedness and complications readiness interventions to increase the use of skilled care at birth and to increase timely use of facility care for obstetric and newborn complications. However, these interventions are complex and relate strongly to the context in which they are implemented. In this article we explore factors to consider when implementing these interventions. Methods This paper reports a secondary analysis of 64 studies on birth preparedness and complication readiness interventions identified through a systematic review and updated searches. Analysis was performed using the Supporting the Use of Research Evidence (SURE) framework to guide thematic analysis of barriers and facilitators for implementation. Results Differences in definitions, indicators and evaluation strategies of birth preparedness and complication readiness interventions complicate the analysis. Although most studies focus on women as the main target group, multi-stakeholder participation with interventions occurring simultaneously at both community and facility level facilitated the impact on seeking skilled care at birth. Increase in formal education for women most likely contributed positively to results. Women and their families adhering to traditional beliefs, (human) resource scarcities, financial constraints of women and families and mismatches between offered and desired maternity care services were identified as key barriers for implementation. Conclusions Implementation of birth preparedness and complication readiness to improve the use of skilled care at birth can be facilitated by contextualizing interventions through multi-stakeholder involvement, targeting interventions at multiple levels of the health system and ensuring interventions and program messages are consistent with local knowledge and practices and the capabilities of the health system.